Relación entre parámetros biométricos y peso seco en insectos acuáticos depredadores de Venezuela - López, Carlos (1996)
Predictive equations were calculated to estimate dry weighl (rom standard length and cephalic length or width for Chaoborus sp. (Diptera) and Corydalus spp. (Megaloptera), two groups of predatory aquatic insects from River Guasare-Limón Basin. western Venezuela. Regression analysis indicated that relationship between biomass and biometric parameters was best expressed by equation W= ab. Although all biometric parameters were highly correlated to dry weight (p <0.01). estimations from length or width of lhe head capsule had higher detenninalion coefficients. The results are similar 10 those found in temperate insects.